(untitled) (Journal of Universal Science Research, 2023)
The article opens with significant role of a strategic sectors with export potential in agriculture. It is obvious that Agriculture represents a strategic economic activity for Uzbekistan. Moreover, in the article the agricultural export statistics of Uzbekistan in recent years and other relevant information are cited.